A METHOD FOR DETERMINING AND EVALUATING WEBOMETRIC INDICATORS OF PUBLIC LIBRARIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The complexity of modern social communications and the transformation of society's information environment create unique competition among public digital libraries to attract readers. Library websites play an important role in managing the activities of digital libraries and improving their position in the information space. In general, the website is considered the "calling card" of the electronic library. It is not only a means of communication between readers and the library, but also a source of information that allows you to evaluate the activities of the library based on information about the use of library website by readers. The purpose of the study is to develop a data processing method to improve the efficiency of evaluating public library information resources and websites. A method and algorithm for expert assessment of a site using fuzzy logic are proposed. The article presents the possibilities of using web analytics to determine webometric indicators of a library website, study user behavior patterns, as well as analysis that improves the functionality of the site. Libraries are offered a comprehensive method for multi-criteria evaluation of websites. The essence of this method is that with this method we can not only evaluate the website in a traditional way, but also get the following useful results: full evaluation of websites, evaluation of websites according to certain criteria, selective comparison and ranking of websites are presented. An analysis of classification criteria for evaluating public library websites is presented. To minimize subjectivity when evaluating a website, the evaluation process can involve not only experts, but also a wider audience through online and offline surveys. In general, assessment of electronic public library websites is necessary not only to determine the rating of libraries, but also to make the right management decisions, as well as to determine the needs and interests of readers.